The Union State of Russia and Belarus as a Center for Reloading the New World on the Biosphere Path of Civilizational Development - А. E. Unitsky (Informaciâ i Innovacii)
The article main goal is research continuation on the development and detailed study of the socio-technological path for a civilizational solution of the critical situation our planet has faced. The key tasks here are import substitution, i.e., technological independence, reducing the energy source export importance for the economy, and the most intensive increase in political, social, technological and economic sovereignty. Moreover, the need in searching for new partners, reorientation exports and imports to new markets, strengthening integration with allied countries (Russia and Belarus), which in fact have confirmed their willingness and ability to collaborate even under strong external pressure — these needs are constantly increasing. The author concerns the creation and application of the Program for Redirecting the Economy of the Union State of Russia and Belarus on the Biosphere Path of Civilizational Development (Program) as the main solution the tasks referred above. The Program can prevent global problems in existing models of civilizational order and the destructive orientation of their technological and social development. The proposed Program is not limited by the Union State boarders and consists of the following biosphere and engineering technologies: relic solar bioenergy; biosphere agriculture; construction technology of cluster-type, pedestrian linear cities; “second level” transport and infrastructure complexes – Unitsky String Transport (uST); non-rocket near space industrialization. These biospheric technologies are complementary. Their complex implementation will make the redirection and global reset of any country economy possible, and primarily the economy of the Union State.